Decadal Changes in Glacier Area, Surface Elevation and Mass Balance for 2000–2020 in the Eastern Tanggula Mountains Using Optical Images and TanDEM-X Radar Data - Yushan Zhou; Xin Li; Donghai Zheng; Xiaolong Zhang; Yingzheng Wang; Shanshan Ren; Yanlong Guo (Remote Sensing, 2022)
The response of lake-terminating glaciers to climate change is complex, and their rapid changes are often closely linked to glacial-lake outburst floods. However, the eastern Tanggula Mountains, which are the only area where lake-terminating glaciers are found within the Tibetan Plateau, have received little attention to date. In this study, to address this gap, we generated updated glacier boundaries and estimated the interdecadal area changes for 2000–2020 based on the interpretation of Landsat-5/8 and Sentinel-2 images. In addition, based on the method of digital elevation model (DEM) differencing, we quantified the changes in glacier thickness and mass balance using TanDEM-X radar data and SRTM DEM over almost the same periods. The final results show that the glaciers in the eastern Tanggula Mountains, as a whole, have experienced accelerated area shrinkage (with a rate of area loss increasing from −0.34 ± 0.83 km2 a−1 to −0.93 ± 0.81 km2 a−1 for 2000–2013 and 2013–2020, respectively) and accelerated ice thinning (changing from −0.19 ± 0.05 m a−1 and −0.53 ± 0.08 m a−1 for 2000−2012 and 2012–2020, respectively). Furthermore, the region-wide glacier mass balance was −0.16 ± 0.04 m w.e. a−1 and −0.45 ± 0.07 m w.e. a−1 for these two sub-periods, corresponding to a 1.8 times acceleration of mass loss rate. The average mass balance during 2000–2020 was −0.23 ± 0.04 m w.e. a−1, which is equivalent to a rate of mass loss of −0.04 Gt a−1. More specifically, within the region, the lake-terminating glaciers have exhibited more significant acceleration of area loss and mass loss, compared to the land-terminating glaciers. However, interestingly, the average thinning rate of the lake-terminating glaciers is always lower than that of the land-terminating glaciers over all study periods, which is in contrast with previous findings in other high mountain areas (e.g., the Himalaya Mountains). Field study and proglacial lakes monitoring suggest that the local topography plays a vital role in the evolution of the glacial lakes in this region, which further affects the glacier changes. Furthermore, the present status of the glacier changes in this region can be attributed to the long-term increase in air temperature. Our findings provide a comprehensive overview of the current state of glacier changes across the eastern Tanggula Mountains and will help to improve the understanding of the heterogeneous response of glaciers to climate change.